Designing the Smile in Complete Denture Patient: An Ingenious Approach - Shreyas Shingane; Swati Rupam; Sakshi Pandey; Sanjeev Singh; Saumya Sharma; Vivek Lath (Journal of Pharmacy and Bioallied Sciences)
Purpose: This innovative technique determines the symmetry of anterior teeth arrangement discrepancies and ascertain the extension of the smile during the procedure of jaw relation procedure performed by prosthodontist. Methods: Smiling images of 20 patients were captured and analyzed using PicsArt© software. Facial midline, canine line, smile line, and other conventional factors were overlaid onto the photographs. Pre-designed smiles were extracted from previous designs and superimposed onto each patient’s photograph. The resulting images were systematically evaluated to enhance aesthetic outcomes, promoting attractiveness, encouraging patient satisfaction during jaw relation. Results: Patients were highly motivated on the day of jaw relation appointment. Prosthodontists were able to evaluate asymmetric smile, midline shift, extension of canines, and other discrepancies. Conclusion: Edentulous patients deserve a superior aesthetic and beautiful smile. Prosthodontist can now will be able to design smiles more easily and in less time before the appointment of try-in. At the same time, dentist will also be able to take approval from the patient regarding the appearance of the smile.